Функції принципів права Європейського Союзу в практиці Суду Європейського Союзу - Юхимюк, О.; Yukhymiuk, O. (Східноєвропейський національний університет імені Лесі Українки, 2019)
Принципи права Європейського Союзу в практиці Суду Європейського Союзу реалізують ряд завдань. Завдяки принципам права можуть вирішуватися питання, не врегульовані правом Європейського Союзу. Створюючи і застосовуючи принципи права, Суд Справедливості фактично реалізує квазі-гармонізацію, яка не лише зближує правові системи держав-членів ЄС, але й країн, що прагнуть до членства в Європейському Союзу.The article presents the results of the functional analysis of the fundamental principles of the European Union Law in the practice of the Court of Justice of the European Union. The lack of specificity and general nature of the content of the norms of EU law, their complete or partial absence, lead to an increase in the importance of the principles of law in the practice of the Court of Justice of the European Union. The principles of the European Union law in practice of the EU Court of Justice facilitate a solution of a number of problems and tasks, which in particular include: filling in gaps in EU law; the integration of the EU legal system as a whole and the legal systems of EU Member States, and those aspiring to EU membership; formation of independent supranational EU legal system. These principles act as an additional, but not a minor, tool for interpreting and applying the founding treaties of the EU, protecting human rights, and promoting the formation of an EU citizenship institute. It is these principles of law that serve as a means of filling the gaps in the law enforcement activities of the EU institutions and directly within the Court of Justice.
The Functions of the European Union Law Principles in the Court of Justice of the European Union Practice
Keywords: принципи права; принципи права ЄС; Суд Справедливості ЄС; principles of law; principles of EU law; EU Court of Justice